Application of microfluidic chips in the simulation of the urinary system microenvironment. (April 2023) - Hou, Changhao; Gu, Yubo; Yuan, Wei; Zhang, Wukai; Xiu, Xianjie; Lin, Jiahao; Gao, Yue; Liu, Peichuan; Chen, Xiang; Song, Lujie
Abstract: The urinary system, comprising the kidneys, ureters, bladder, and urethra, has a unique mechanical and fluid microenvironment, which is essential to the urinary system growth and development. Microfluidic models, based on micromachining and tissue engineering technology, can integrate pathophysiological characteristics, maintain cell-cell and cell-extracellular matrix interactions, and accurately simulate the vital characteristics of human tissue microenvironments. Additionally, these models facilitate improved visualization and integration and meet the requirements of the laminar flow environment of the urinary system. However, several challenges continue to impede the development of a tissue microenvironment with controllable conditions closely resemble physiological conditions. In this review, we describe the biochemical and physical microenvironment of the urinary system and explore the feasibility of microfluidic technology in simulating the urinary microenvironment and pathophysiological characteristics in vitro . Moreover, we summarize the current research progress on adapting microfluidic chips for constructing the urinary microenvironment. Finally, we discuss the current challenges and suggest directions for future development and application of microfluidic technology in constructing the urinary microenvironment in vitro . Graphical abstract: Image 1